PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PROBLEM BASED LEARNING (PBL) MENGGUNAKAN KONTEKS WISATA ALAM BUKIT COGONG LESTARI PADA MATERI BANGUN DATAR KELAS IV SD NEGERI WONOKERTO - Reti Fitri Yani; Drajat Friansah; Yufitri Yanto (Jurnal Perspektif Pendidikan, 2023)
This study aims to develop problem-based learning worksheets on flat shape materials that are valid and practical and have potential effects. This research is a research development research using the stages of the ADDIE model, namely Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study included validators (linguists, material experts and media experts), class teachers and fourth grade students. Data collection techniques were carried out by means of interviews, questionnaires and tests. Based on the research results the developed worksheet has a language validation of 0.83 with a very valid category, material validation of 0.61 with a valid category, and a media expert validator of 0.71 with a valid category and a one-to-one test of 0.93 with a category very valid. The practicality of worksheets based on the teacher's response was 90.90% in the very practical category and the student response (small group) was 92.81% in the very practical category. While the potential effect of LKS on learning outcomes is 80.95% in the very good category. Based on these data it can be concluded that the problem-based learning worksheet on the flat material developed in this study is valid and practical and has a very good potential effect so that it can be used in learning on the flat material.